Fulminant Type 1 Diabetes Mellitus Caused by Drug Reaction With Eosinophilia and Systemic Symptoms (DRESS): A Case Report and Review of the Literature - Zhu, Bizhen; Wu, Jinzhun; Chen, Guobing; Yang, Yungang; Yi, Cuili (Frontiers in Endocrinology, 2019)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare, severe cutaneous adverse drug reaction characterized by fever, skin rashes, lymphadenopathy, leukocytosis with eosinophilia and/or atypical lymphocytosis, and multiple visceral organ involvement. Moreover, Patients with DRESS are meanwhile at risk of developing autoimmune diseases including thyroiditis, diabetes mellitus and SLE after the initial remission. Early recognition of DRESS and its long-term sequelae will enable to initiate proper intervention timely. We described a 9-month boy who was admitted to our hospital because of severe pneumonia and developed DRESS 3 weeks later. In addition, we performed a literature review of diabetes mellitus associated with DRESS by searching the PubMed. A total of 16 articles and 27 related case reports were obtained between 2001 and 2018. The mean age was 46yr. The duration from the onset of DRESS to the development of DM was 21d on average. 21 patients were diagnosed F1TD, 5 patients were confirmed T1DM, and 1 patient was defined T2DM. GAD were detected in 4 cases. Of 22 cases in which virus examination were carried out, evidence of virus reactivation was established in 16 cases (72.7%). Of patients with F1TD, 16 (88.9%) were evidenced reactivation of herpes virus. High frequency of HLA genotype and haplotype were also found in 11 cases. No patients died from the disease. The aim of this work is to raise awareness of long-term autoimmune sequelae in patients with the syndrome for physician. Long-term follow-up is strongly recommended for those patients.